How does the way we design hotels influence consumer brand experiences. Issue 3 (1st September 2019) - Beka, Rudin; Cenko, Enila
The influence that product design has on commercial success is undisputable. A considerable number of companies highly invest in creativity and design by forging partnerships with contemporary artists and design studios so as to create impressive commercial brands. Unusual design spaces are shaping our consumption experiences and influencing the way we evaluate and talk about brands. The main idea of this study is to approach customers' brand experience from a design perspective. How can we bring empathy to customers within the hotel industry by using impressive design and how can we manipulate environmental design so as to enhance positive brand experiences? The research is focused on theoretical and practical work in the field of design and marketing, approaching a design perspective within the brand experience process. A detailed analysis is conducted on hotel spatial branding and a model has been constructed using pleasant emotions as mediators. The findings indicate that products with a focus on symbolic design are expected to have a higher customer brand experience. The proposed model can have practical and managerial applications in the area of environmental psychology, hotel design, branding strategy and integrated marketing communications where the recognition of design benefits will have a direct contribution to business performance.